1982
DOI: 10.1128/mcb.2.11.1372
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of integration of DNA microinjected into cultured mammalian cells: evidence for homologous recombination between injected plasmid DNA molecules.

Abstract: We examined the fate of DNA microinjected into nuclei of cultured mammalian cells. The sequence composition and the physical form of the vector carrying the selectable gene affected the efficiency of DNA-mediated transformation. Introduction of sequences near the simian virus 40 origin of DNA replication or in the long terminal repeat of avian sarcoma provirus into a recombinant plasmid containing the herpes simplex virus thymidine kinase gene (pBR322/HSV-tk) enhanced the frequency of transformation of LMtk-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
250
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 397 publications
(274 citation statements)
references
References 29 publications
21
250
1
1
Order By: Relevance
“…56,70 Many studies on SV40 transformed cell lines reported sustained instability involving the SV40 sequences and flanking cellular DNA upon continued culturing, 56,[71][72][73] suggesting that integrated structures are often unstable immediately after integration, and that this instability can persist in the absence of selection. While in some cases, tandem arrays of transgenes remain stable following integration, 41 other groups have observed homologous recombination between copies within the array, which lead to changes in structure, expression, and transgene copy number 74,75 (see also our unpublished results).…”
Section: Recipient Genomic Loci Are Often Unstable After Illegitimatesupporting
confidence: 53%
See 4 more Smart Citations
“…56,70 Many studies on SV40 transformed cell lines reported sustained instability involving the SV40 sequences and flanking cellular DNA upon continued culturing, 56,[71][72][73] suggesting that integrated structures are often unstable immediately after integration, and that this instability can persist in the absence of selection. While in some cases, tandem arrays of transgenes remain stable following integration, 41 other groups have observed homologous recombination between copies within the array, which lead to changes in structure, expression, and transgene copy number 74,75 (see also our unpublished results).…”
Section: Recipient Genomic Loci Are Often Unstable After Illegitimatesupporting
confidence: 53%
“…In some cases, however, instability appears to be restricted to the time of integration. Many studies carried out in cultured cells 41,47,48,53 and transgenic mouse lines 43 have shown that while vectors can be physically rearranged initially, expansion of cell or mouse lines reveals no further rearrangements. This leads to the conclusion that the deletions and rearrangements observed are sometimes early events in the integration process.…”
Section: Recipient Genomic Loci Are Often Unstable After Illegitimatementioning
confidence: 99%
See 3 more Smart Citations